Effects of warm ischaemia combined with cold preservation on the hypoxia‐inducible factor 1α pathway in an experimental renal autotransplantation model. Issue 13 (21st October 2014) - Delpech, P. O.; Thuillier, R.; Le Pape, S.; Rossard, L.; Jayle, C.; Billault, C.; Goujon, J. M.; Hauet, T.
<x xml:space="preserve">Abstract</x> Background The increased use of marginal donors highlights the importance of organ quality in transplantation and the identification of prognostic biomarkers. This experimental study investigated modulation of the hypoxia‐inducible factor (HIF) 1α pathway in kidney grafts in relation to different degrees of ischaemia. Methods In a porcine autotransplantation model, two different kidney graft protocols were compared: standard 24‐h cold storage (CS) and 24‐h CS preceded by 1 h warm ischaemia (WI + CS). The renal HIF‐1α pathway and tubular dedifferentiation were analysed in the early phase of reperfusion and at 3 months. Results There was a relationship between the degree of ischaemic injury and the outcome of the kidney graft. During the first week of reperfusion, WI + CS grafts showed a higher degree of injury. The observed tubular dedifferentiation was associated with delayed HIF‐1α expression, and with loss of its role in transcription. In highly injured kidneys, deregulation of the HIF‐1α pathway was also observed in the chronic phase, with reduced production of vascular endothelial growth factor (VEGF) A, and upregulation of VEGF receptor 1 (Flt‐1) and thrombospondin 1. In addition, these kidneys displayed altered kidney histology and decreased function. Conclusion The HIF‐1α pathway appears to be abolished early in response to severe ischaemia. A high degree of ischaemic injury also results in chronic activation of the HIF‐1α pathway, diverting it away from the beneficial activation of angiogenesis. Further studies on the finely tuned balance of signals in this pathway may provide diagnostic biomarkers that can determine organ quality during kidney transplantation. <boxed-text content-type="box" id="bjs9611-blkfxd-0001" position="anchor" orientation="portrait"> Surgical relevance The increased use of marginal donors has highlighted the importance of organ quality in transplantation. Renal ischaemia–reperfusion injury following transplantation induces graft dysfunction. In a porcine model of renal autotransplantation, the induction of regenerative processes, in response to graded degrees of ischaemia, was studied in the post‐transplantation phase. There was early abrogation of the hypoxia‐inducible factor (HIF) 1α pathway in response to severe ischaemia. High degrees of ischaemic injury induced chronic activation of the HIF‐1α pathway, diverting it from the beneficial activation of angiogenesis. Identification of the mechanisms involved in renal regeneration, such as those related to the HIF‐1α pathway, are important as these mechanisms can be used to identify novel therapeutic targets or develop diagnostic biomarkers to determine organ quality early in the transplantation process. </boxed-text>